(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Fajrih N, Wiryawan KG, Sumiati, Syahpura SK, Winarsih W. 2022. Identification of bioactive compounds of banana corm (Musa paradisiaca) using GC-MS and its inhibitory effect against pathogenic bacteria. Biodiversitas 23: 195-204. The banana corm is an agricultural waste that is abundant in nature but is rarely used even though it has many benefits including as an antibacterial agent. Therefore, this study aims to identify and isolate antibacterial compounds in banana corm and evaluate their antibacterial activity against pathogenic bacteria (E. coli, S. aureus, S. typhi, B. cereus) that generally infect livestock. The extraction procedure was carried out by maceration using ethanol and fractionation through the liquid-liquid method using ethyl acetate. The ethyl acetate fraction was further analyzed using column chromatography using silica gel as a stationary phase and eluted with 100% of CHCl?, 20% of MeOH/CHCl?, 3% of MeOH/CHCl? and 100% of MeOH, respectively. Identification of antibacterial compounds was carried out using GC-MS. Growth inhibitory activity against pathogenic bacteria was conducted by the well agar diffusion method. Based on the GC-MS chromatogram results, several compounds with antibacterial properties compounds were identified in the banana corm, namely Octadeca-9,12-Dienoicand Hexadecanoic acids. The extract of banana corm has antibacterial activity against E. coli, Salmonella typhi, S. aureus, and B. cereus at the concentration of 5% with inhibitory zones of 5.88 mm (moderate), 9.13 mm (moderate), 13.86 (strong), and 14.66 (strong), respectively. It is concluded that banana corm extract contains antibacterial compounds and can inhibit the growth of several pathogenic bacteria.